Expiratory muscle endurance in chronic obstructive pulmonary disease. Issue 2 (1st February 2002) - Ramírez-Sarmiento, A; Orozco-Levi, M; Barreiro, E; Méndez, R; Ferrer, A; Broquetas, J; Gea, J
Abstract : Background: A reduction in expiratory muscle (ExM) endurance in patients with chronic obstructive pulmonary disease (COPD) may have clinically relevant implications. This study was carried out to evaluate ExM endurance in patients with COPD. Methods: Twenty three patients with COPD (FEV1 35 (14)% predicted) and 14 matched controls were studied. ExM endurance was assessed using a method based on the use of an expiratory threshold valve which includes two steps. In step 1 the load is progressively increased (50 g every 2 minutes) until task failure is reached, and the pressure generated against the highest tolerated load is defined as the maximal expiratory sustainable pressure (Pthmax). In step 2 subjects breathe against a submaximal constant load (80% of Pthmax) and the time elapsed until task failure is termed the expiratory endurance time (Tth80 ). In addition, the strength of peripheral muscles (handgrip, HGS) and respiratory muscles (maximal inspiratory and expiratory pressures, Pi max and Pe max, respectively) was evaluated. Results: Patients with COPD had lower ExM strength and endurance than controls: Pe max 64 (19)% predicted v 84 (14)% predicted (mean difference 20%; 95% confidence intervals (CI) 14 to 39); Pthmax 52 (27) v 151 (46) cm H2 O (mean difference 99, 95% CI 74 to 123); and Tth80 9.4 (6.3) v 14.2 (7.4) min (mean difference 4.8, 95% CI 1.0 to 10.4; p<0.01 for all). Interestingly, ExM endurance directly correlated with both the severity of airways obstruction (Pthmax with FEV1, r =0.794, p<0.01) and the reduction in strength observed in different muscle groups (Pthmax with HG, Pi max or Pe max, r =0.550, p<0.05; r =0.583, p<0.001; and r =0.584, p<0.001, respectively). Conclusions: ExM endurance is decreased in patients with COPD. This impairment is proportional to the severity of the disease and is associated with lower strength in different muscle groups. This suggests that systemic effects are implicated in the impairment observed in ExM function.